Sami perspectives in school leadership? Conspicuous by their absence! - Jones, Mari-Ana; Lund, Sandra; Sahlin, Susanne (Mittuniversitetet, Institutionen för utbildningsvetenskap, 2025)
“Why is it so difficult to get the Sami teachers to come to staff meetings?” asked one school leader inNorway. Imbued with frustration and suspicion, this question highlights the difficulties with ongoingreconciliation work with Sami peoples in schools in Norway and Sweden, confirmed by our experiencesas educators of school leaders and by an exploration of existing policy and literature. There is a lack ofunderstanding of the needs and interests of school communities situated in Sami districts. Dominantknowledge about school leadership in Norway and Sweden takes no account of Sami perspectives andschool leaders are not afforded opportunities to develop the necessary culturally sensitiveunderstandings. We propose that researchers should focus more on the vital work of school leaders,seeking to create knowledge and practices which support, rather than hinder, reconciliation.